Barriers associated with pulse and plant-based meat alternative consumption across sociodemographic groups: a Capability, Opportunity, Motivation, Behaviour model approach - Kuosmanen, Sini; Niva, Mari; Pajari, Anne-Maria; Korhonen, Kirsi; Muilu, Toivo; Konttinen, Hanna (Frontiers in Nutrition, 2023)
Introduction: Meat consumption should be reduced to enhance environmental sustainability and food security. Pulses and other plant-based protein sources provide an alternative to meat, but their consumption remains low. To enhance environmental sustainability and food security, there should be a change in dietary protein consumption. It is suggested that meat consumption should be reduced and that the currently low consumption of pulses and other plant-based proteins should increase. We aimed to examine 1) how sociodemographic factors and perceived barriers are associated with selfreported current and perceived future pulse and other plant-based meat alternative (PBMA) consumption and 2) how sociodemographic factors relate to perceived barriers. Methods: Participants were 18-75-year-old Finnish adults (n=1000). Multivariable logistic regression was used as the main analysis technique. The results were interpreted by employing the Capability, Opportunity, Motivation, Behaviour (COM-B) model.Results: Pulses were consumed more often than PBMAs and lower education level and financial strain were associated with more infrequent pulse and PBMA use. The most common perceived barriers for pulse consumption were unfamiliarity, expensive price, and unpleasant taste, which can be interpreted to represent the capability, opportunity and motivation components of the COM-B model, respectively. Women, the young, and financially strained perceived more barriers limiting their pulse consumption than others.Discussion: To increase plant-based food consumption, it is important that tasty, easy to use and affordable plant-based foods are available for all. Additionally, we suggest that food services should be encouraged to increase the use of pulses in their dishes and that capabilities, opportunities and motivations are taken into account in intervention measures advancing plant protein consumption.